Modigliani, Picasso And André Salmon - Jean Cocteau (NC, 2026)
Modigliani, Picasso and André Salmon in front of the Café de la Rotonde, Paris.
Droits : Licence indiquee par Wikimedia Commons
Keywords: peinture; peintres; artistes peintres; picasso; photo; archives photographiques; photographie; Art